PERSEPSI GURU AGAMA TERHADAP TINGKAT EKSISTENSI BANK SYARIAH DI KECAMATAN KOTA TENGAH PROVINSI GORONTALO - Laras Ayu Sekarrini (Elsia: Jurnal Psikologi Manusia, 2024)
The aim of this research is to analyze the extent of perceptions regarding the existence of Sharia Banks in Kota Tengah District, Gorontalo City. The method used in this research is qualitative research. The researcher used an interview method with religious teachers in Kota Tengah District, Gorontalo City.then from the research results it was found that the perceptions of religious teachers regarding Sharia Banks were reviewed from 3 aspects, namely Sharia Bank products, Sharia Bank Services and Sharia Bank Socialization.Firstly, in terms of Sharia Bank products, all religious teachers in the Kota Tengah District of Gorontalo City know about Sharia Banks and their products only to the extent of their sharia, such as the halal-haram prohibitions on interest or usury. Second, in terms of Sharia Bank services, religious teachers are of the opinion that services at Sharia Banks are still unsatisfactory and quite difficult. Third, in terms of socialization, the potential for the entry of sharia banks in the form of educational institutions in Gorontalo, especially in Central City and also in its predominantly Muslim community, has not been fully explored by sharia banking in Gorontalo.